Methodologies for the Seismic Performance Assessment of Bridges – Application to bridges in Portugal - Lopes, L. (2010)
On the last two decades seismic behaviour assessment turned from force based analysis to displacement based criteria. The purpose of this work is to provide some practical support in order to incorporate the new performance based methodologies in the bridge design. These methodologies are mainly nonlinear static analysis, where structure deformation levels were imposed through the application of an increasing lateral horizontal load. There are different procedures supported by nonlinear static analysis. In this paper, only the Capacity Spectrum Method is mentioned. The presented examples include some current reinforced concrete bridges of small to medium dimension and allowed the analysis of the influence of some characteristics like the skewness, structures irregularities and the type of connection between the deck and the piers.